Stable correction of a genetic deficiency in human cells by an episome carrying a 115 kb genomic transgene. - Wade-Martins, R; White, R; Kimura, H; Cook, P; James, MR (2000)
Persistent expression of a transgene at therapeutic levels is required for successful gene therapy, but many small vectors with heterologous promoters are prone to vector loss and transcriptional silencing. The delivery of genomic DNA would enable genes to be transferred as complete loci, including regulatory sequences, introns, and native promoter elements. These elements may be critical to ensure prolonged, regulated, and tissue-specific transgene expression. Many studies point to considerable advantages to be gained by using complete genomic loci in gene expression. Large-insert vectors incorporating elements of the bacterial artificial chromosome (BAC) cloning system, and the episomal maintenance mechanisms of Epstein-Barr virus (EBV), can shuttle between bacteria and mammalian cells, allowing large genomic loci to be manipulated conveniently. We now demonstrate the potential utility of such vectors by stably correcting a human genetic deficiency in vitro. When the complete hypoxanthine phosphoribosyltransferase (HPRT) locus of 115 kilobases (kb) was introduced into deficient human cells, the transgene was both maintained as an episome and expressed stably for six months in rapidly dividing cell cultures. The results demonstrate for the first time that gene expression from an episomal genomic transgene can correct a cell culture disease phenotype for a prolonged period.